2017
DOI: 10.1063/1.4996695
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale simulations of confined Nafion thin films

Abstract: The morphology and transport properties of thin films of the ionomer Nafion, with thicknesses on the order of the bulk cluster size, have been investigated as a model system to explain the anomalous behaviour of catalyst/electrode-polymer interfaces in membrane-electrode assemblies. We have employed dissipative particle dynamics (DPD) to investigate the interaction of water and fluorocarbon chains with carbon and quartz as confining materials for a wide range of operational water contents and film thicknesses.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…In order to clarify the origin of the interfacial resistance, Jinnouchi et al 24 and Kurihara et al 25 performed molecular dynamics (MD) simulations and showed that the interfacial resistance originates from the dense ionomer layer created at the ionomer/Pt interface. By contrast, a more significant bulk ionomer resistance was recently proposed on the basis of hydrogen pump experiments 26 and a mesoscopic CL model 27 assuming highly reduced transport in thin films compared to that in bulk ionomers because of confinement effects 28 or substrate interactions 29 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In order to clarify the origin of the interfacial resistance, Jinnouchi et al 24 and Kurihara et al 25 performed molecular dynamics (MD) simulations and showed that the interfacial resistance originates from the dense ionomer layer created at the ionomer/Pt interface. By contrast, a more significant bulk ionomer resistance was recently proposed on the basis of hydrogen pump experiments 26 and a mesoscopic CL model 27 assuming highly reduced transport in thin films compared to that in bulk ionomers because of confinement effects 28 or substrate interactions 29 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Other types of important polymeric materials are the hydrated selectively permeable membranes (particularly the Nafion membranes), which play a crucial role in fuel cells. Their study has represented a hot topic for experimentalists [266,267], theoreticians and computer scientists for several decades, and it is not surprising that several recent DPD studies have addressed the fuel cell membranes [124,253,[268][269][270][271][272][273]; the last two papers unfortunately study the electrically charged system without explicit electrostatics, which restricts their impact. On the other hand, the papers on hydrated membranes published by the Neimark group [124,271,273] are of special interest because they also contribute significantly to the methodological progress in DPD modelling.…”
Section: Experiment-inspired and Application-orientated Papersmentioning
confidence: 99%
“…Further applications involving dl meso dpd as the DPD simulation engine have made use of the same technique of parameterising conservative interactions by finding energies of mixing or Hildebrand solubility parameters using atomistic molecular dynamics or Monte Carlo simulations. These include systems involving carbon nanotubes [100,101], Nafion [102][103][104], block copolymers with poly(carboxybetaine) and poly(ethylene glycol) [105], poly(amido amine) (PANAM) dendrimers and single-stranded DNA [106], poly(methyl methacrylate-co-butyl acrylate-co-styrene) for strengthening fragile papers [107], channel membranes of polystyrene-block -poly(4-vinyl pyridine) block copolymer [108] and phase behaviour of sophorolipids [109].…”
Section: Work Carried Out Using DL Meso Dpdmentioning
confidence: 99%